Tandem nozzle supersonic wind tunnel design. (1st January 2013) - Wu, Jie; Radespiel, Rolf
A new tandem nozzle supersonic wind tunnel was designed for Technische Universität Braunschweig. Based on the infrastructure of the existing M = 6 Ludwieg tube in Braunschweig (HLB), two nozzles in tandem configuration are designed to get supersonic flow with a similar test section size. Preliminary design trades are presented based on one-dimensional flow analysis. Using alternate methods, contours of the second nozzle are designed. Numerical optimisations of the second nozzle are accomplished using the DLR TAU-Code, by which reliable estimates of flow uniformity in the test section are obtained. A settling chamber with suitable flow straighteners is also employed. The flow analysis determines a reasonable configuration of the overall tandem nozzle wind tunnel and yields realistic estimates of flow uniformity in the test section. In conclusion the present work provides quantitative design trades, detailed flow quality and performance data for cost-efficient extensions of hypersonic Ludwieg tubes into the supersonic flow range.